Fok I and Bsm I gene polymorphism of vitamin D receptor and essential hypertension: a mechanistic link - Richa Awasthi; Priyanka Thapa Manger; Rajesh Kumar Khare (BMC, 2023)
Abstract The vitamin D receptor (VDR) gene serves as a good candidate gene for susceptibility to essential hypertension. The gene regulates the renin angiotensin system by influencing blood pressure regulation. Around 3% of the human genome is regulated by the vitamin D endocrine system. Several studies have reported mixed results with respect to relationship of VDR gene and hypertension. Observational evidence supports the concept that vitamin D plays a role in the pathogenesis of cardiovascular disease and arterial hypertension which is further supported by meta-analysis and case control studies reporting how VDR polymorphism leads to the onset and development of hypertension. In this review, we summarize the existing literature on the link between VDR and hypertension, including mechanistic studies, observational data, and clinical trials showing relationship of vitamin D level and hypertension with a focus on recent findings related to genetic studies that showed the relationship of VDR gene polymorphism with vitamin D level in hypertensive and normotensive groups. As a result, determining the association of VDR polymorphisms with essential hypertension is expected to aid in the risk assessment for the condition.